2020
DOI: 10.1111/jop.13113
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 induces amoeboid‐to‐mesenchymal transition of CD44high oral squamous cell carcinoma cells via miR‐422a downregulation through ERK activation and Cofilin‐1 phosphorylation

Abstract: Background The objective of this study was to clarify the molecular mechanism of amoeboid‐to‐mesenchymal transition (AMT) of CD44high oral squamous cell carcinoma (OSCC) cells. Methods Morphology and expression of mesenchymal genes were investigated in CD44high OSCC cells (CD44high OM‐1 cells) cultured on laminin‐coated soft silicone gel. Additionally, microarray analysis was performed to investigate microRNA (miRNA) expression inhibited by transforming growth factor‐β1 (TGF‐β1) in CD44high OM‐1 cells. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 28 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, we previously found that TGF-β1 induced amoeboid-to-mesenchymal transition in CD44 high OSCC cells by inhibition of miR-422a [6]. Thus, miR-422a may be essential for the maintenance of amoeboid-like CD44 high OSCC cells [6]. In this study, we demonstrated that miR-224-5p-induced downregulation of PANX1 conferred apoptotic resistance in CD44 high OSCC cells.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Furthermore, we previously found that TGF-β1 induced amoeboid-to-mesenchymal transition in CD44 high OSCC cells by inhibition of miR-422a [6]. Thus, miR-422a may be essential for the maintenance of amoeboid-like CD44 high OSCC cells [6]. In this study, we demonstrated that miR-224-5p-induced downregulation of PANX1 conferred apoptotic resistance in CD44 high OSCC cells.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, miR-218-5p suppresses invasion by OSCC cells through inhibiting expression of CD44 [27]. Furthermore, we previously found that TGF-β1 induced amoeboid-to-mesenchymal transition in CD44 high OSCC cells by inhibition of miR-422a [6]. Thus, miR-422a may be essential for the maintenance of amoeboid-like CD44 high OSCC cells [6].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations